(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article examines the theoretical foundations of the development of the socio-economic system of small business, the concept of the system, the research and approaches of scientists to the concepts of small business and entrepreneurship . Different classifications of socio-economic systems are given. The concepts of business and entrepreneurship are also discussed in a personal approach to the factors influencing the development of small business and private entrepreneurship. Then the analysis of factors influencing the harmonious development of the regions of Uzbekistan was carried out increased blood .